Peran Guru Agama dalam Menanamkan Pendidikan Karakter yang Berbasis Nilai Agama dan Budaya Sasak pada Siswa Kelas VI SDN 5 Ampenan Kota Mataram - Zaenal Abidin (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to examine the role of Islamic religious teachers in instilling character education based on religious values and Sasak culture in sixth-grade students at SDN 5 Ampenan, Mataram City. Character education is a fundamental pillar in shaping students' personalities, and religious teachers occupy a strategic position in this process, especially within the context of the Sasak community, which is rich in Islamic values and local wisdom. This study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Research subjects included the principal, the Islamic Education (PAI) teacher, and sixth-grade students. Findings reveal that religious teachers serve as: (1) educators and instructors of Islamic values; (2) moral role models grounded in Sasak culture; (3) motivators in the internalization of values such as tata krama (etiquette), titi (prudence), and tatas tuhu trasna (honesty, loyalty, and compassion); and (4) facilitators of religious and local cultural activities. Supporting factors include principal support, an Islamic school environment, and preserved local wisdom. Inhibiting factors include social media influence and a lack of Sasak culture-based learning resources. This study recommends the systematic integration of Sasak cultural values into the Islamic religious education curriculum at the primary school level.